A first assessment of organic carbon burial in the West Gironde Mud Patch (Bay of Biscay). (15th May 2021) - Dubosq, Nicolas; Schmidt, Sabine; Walsh, J.P.; Grémare, Antoine; Gillet, Hervé; Lebleu, Pascal; Poirier, Dominique; Perello, Marie-Claire; Lamarque, Bastien; Deflandre, Bruno
Abstract: On the Bay of Biscay continental shelf, there are several mid-shelf mud patches including La Grande Vasière to the north, the West Gironde Mud Patch (WGMP) off the Gironde estuary and the Basque Mud Patch close to the Spanish border. In general, these deposits are several meters thick and cover coarser substrate. Questions remain about their storage capability for fine particles and carbon. This work investigates the sedimentation of the WGMP in order to develop a first estimate of organic carbon (OC) burial. Interface sediment cores were collected at nine stations along two cross-shelf transects in October–November 2016. X-radiograph imaging and grain-size analyses were used to characterize sedimentary structures. 210 Pbxs depth profiles were established to calculate sediment (SAR) and mass (MAR) accumulation rates. Sedimentary structures indicate episodic sandy inputs overlying older deposits at proximal sites, and relatively continuous sedimentation at seaward locations. On the outer-central portion of the northern transect, a maximum SAR (0.47 cm yr −1 ) was observed, suggesting a depocenter. On the southern transect, excluding two stations where sedimentary inputs appear massive but sporadic, the SARs are lower (<0.3 cm yr −1 ). Quantitative estimates of OC burial rates increase seaward with a maximum of 45 gC m −2 yr −1 . To evaluate carbon loading independent of grain-size variability, OC values were normalized to surface area of sediments (SA). Interestingly, a qualitative comparison of OC burial efficiencies using the OC/SA ratio highlights three groups of sites (low, medium and relatively high OC burial efficiency) which are likely related both to different sedimentary environments and variable deposition conditions linked to local environmental conditions and depth. This work highlights the likely control of hydrodynamic intensity and sedimentary inputs on the amount of OC stored in the WGMP sediments. Highlights: - The West Gironde Mud Patch can be divided in three deposition areas - Organic carbon (OC) burial rates increase seaward with a maximum of 45 gC m −2 yr −1 - Hydrodynamic seems to control organic carbon burial at a multi-decennial scale - OC burial rates and efficiencies vary depending on bathymetry